Effectiveness of three chemical solutions on gutta-percha cones by rapid sterilization technique: A scanning electron microscope study - S Anitha Rao; Muppala Nikhitha Chowdary; C S Soonu; T Muralidhar (Wolters Kluwer Medknow Publications, 2019)
Objectives: It is prudent to produce most sterile root canal system and to maximize the most hermetical seal so gutta percha cones are used gutta-percha (GP) cones are used to obliterate the root canal space, prevention of contamination becomes a problem. Hence, the aim of this study was to identify the presence of surface topography, crystallization, and subsequent removal of sodium hypochlorite, glutaraldehyde, and aloe vera crystals on GP cones after rapid sterilization technique - this was a scanning electron microscope (SEM) study. Materials and Methods: GP points of size 80 and 2% taper were divided into four groups depending on the type of agents used for sterilization. Four groups were as follows: Group 1 - control group, Group 2 - aloe vera, Group 3 - glutaraldehyde, and Group 4 - NaOCL. About 10 GP points of each group were immersed for 2 min in different concentrations and observed under SEM to evaluate surface topography and presence of chloride crystals. Statistical analysis was carried out using Chi-square test, Kruskal-Wallis test and Mann-Whitney U-test to compare the results between the groups. All the data were expressed as mean ± standard deviation, and the difference of P < 0.05 or more was considered significant. Results: Aloe vera found to be an effective medium in decontaminating GP cones compared to glutaraldehyde and NaOCL (sodium hypochlorite). Conclusion: The use of sterile GP cones for the obliteration of root canals is of prime importance, and aloe vera group shows no changes in surface topography and the presence of chloride crystal formation compared to the control group. Hence, it is prudent to produce the most sterile root canal system, maximizing most hermetical seal possible.